1999
DOI: 10.1109/59.744552
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of corrective switching in transmission systems

Abstract: This paper reviews several publications on the use of switching operations as a control means to relieve overload in transmission lines/transformers or to solve voltage problems. Previous research efforts dealing with the subject are analysed in relation to the objective of the manoeuvre, priority of this kind of action in relation to the others available and the search procedure employed, besides other implementation details.Some practical issues related to switching as a control option are also addressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 16 publications
(35 reference statements)
0
56
0
4
Order By: Relevance
“…It has been observed that these cuts can be almost linearly dependent on one another, and hence can lead to numerical difficulties with rounding error. Regrettably, the addition of 10 The problem with j = 13 was terminated suboptimally after 40 hours. 11 As an indication of how large this problem is, the outstanding problem is the 359,422 nd subproblem of the original partition, and the 958 th partition of this subproblem.…”
Section: Practical Solution Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that these cuts can be almost linearly dependent on one another, and hence can lead to numerical difficulties with rounding error. Regrettably, the addition of 10 The problem with j = 13 was terminated suboptimally after 40 hours. 11 As an indication of how large this problem is, the outstanding problem is the 359,422 nd subproblem of the original partition, and the 958 th partition of this subproblem.…”
Section: Practical Solution Difficultiesmentioning
confidence: 99%
“…Larger values of j were deemed impractical for this solution technique because the solution times appeared to be growing exponentially. 10 Using the solution for j = 12 as a feasible starting point, various techniques (outlined in the appendix) were used to create and solve subproblems in which certain binary variables were fixed to zero or one. These subproblems were solved either to optimality (at which point the solutions with suboptimal objective functions were discarded) or split into more subproblems in an attempt to find the optimal solution of the original problem.…”
Section: Practical Solution Difficultiesmentioning
confidence: 99%
“…Pgi,Qgi,sij ,ei,fi i∈G c gi P gi (1) where P gi denotes the active power of generator i, and c gi is its cost. The OTS problem is subject to the following constraints:…”
Section: Ots Problem Formulation As a Minlpmentioning
confidence: 99%
“…Network switching operations have been studied in the context of Optimal Power Flow (OPF) problems for various purposes (e.g., overload removal [4], [5], undervoltages/overvoltages alleviation [5], power loss reduction [6], [7], N-1 security improvement [8], generation dispatch cost reduction [3], [9], [10], [11], [12], [13], [14], etc.). The survey papers [1], [2], [3] provide extensive literature on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation